The Implementation of Digital Learning in Language Education: Opportunities, Challenges, and Pedagogical Impacts - I Gusti Ngurah Bagus Yoga Widiadnya (IKIP SARASWATI TABANAN, 2026)
The rapid advancement of digital technology has significantly transformed educational practices, including language learning. Digital learning provides opportunities for interactive, flexible, and learner-centered instruction that enhances language acquisition processes. This study examines the role of digital learning in language education, focusing on its pedagogical benefits, challenges, and impacts on learners’ linguistic competence. Using a qualitative descriptive research design supported by literature analysis and classroom observations, this research explores how digital platforms, applications, and online resources facilitate language learning skills such as reading, writing, listening, and speaking. The findings indicate that digital learning promotes learner autonomy, increases motivation, and supports collaborative learning environments. However, challenges such as digital literacy gaps, unequal access to technology, and instructional design issues remain significant concerns. The study concludes that effective integration of digital learning in language education requires pedagogical readiness, institutional support, and continuous professional development for teachers. These findings contribute to the growing body of research on digital pedagogy and provide recommendations for educators and policymakers in optimizing technology-enhanced language instruction.